2009
DOI: 10.1542/peds.2008-2921
|View full text |Cite
|
Sign up to set email alerts
|

The Future of Health Insurance for Children With Special Health Care Needs

Abstract: Health insurance coverage has the potential to secure access to needed care and improve the quality of life for these children while protecting their families from financially burdensome health care expenses. Continued vigilance and advocacy for children and youth with special health care needs are needed to ensure that these children have access to adequate coverage and that they fare well under health care reform.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
0
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 59 publications
1
12
0
1
Order By: Relevance
“…Past studies have demonstrated that many of these factors or variables are statistically significant predictors of underinsurance, 4 and there is substantial variation in the prevalence of these variables across states. 18 Like previous studies, our analysis of the current data showed that underinsurance is more prevalent among vulnerable populations, including children with more significant functional limitations, those who live in poverty, and those in non-English-speaking households; however, our multivariate adjustment for these variables and others operating at the level of the child and family did not appreciably diminish state disparities in underinsurance.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…Past studies have demonstrated that many of these factors or variables are statistically significant predictors of underinsurance, 4 and there is substantial variation in the prevalence of these variables across states. 18 Like previous studies, our analysis of the current data showed that underinsurance is more prevalent among vulnerable populations, including children with more significant functional limitations, those who live in poverty, and those in non-English-speaking households; however, our multivariate adjustment for these variables and others operating at the level of the child and family did not appreciably diminish state disparities in underinsurance.…”
Section: Discussionsupporting
confidence: 67%
“…If policy makers are interested in ensuring equitable treatment in the health care system for CSHCN, then policy initiatives aimed at reducing underinsurance and increasing uniformity of coverage across states are also needed. A recent report 18 showed that the sources of underinsurance vary by type of coverage, with inadequate coverage of needed services and providers being the primary source of underinsurance for publicly insured CSHCN and inadequate coverage of a reasonable amount of costs being the primary source of underinsurance for privately insured CSHCN. Hence, different approaches to addressing underinsurance in public and private plans may be needed.…”
Section: Discussionmentioning
confidence: 99%
“…Although children with chronic health problems have far higher-than-average costs, fewer than half received a dental visit during the year, and other research has documented that many experience unmet needs in Medicaid/CHIP. 31 Because such a large proportion of the high spenders have hospital stays and emergency room visits, states may be able to reduce the costs associated with stays and visits that could have been avoided if more timely and appropriate ambulatory care had been provided. 32,33 More research is needed on the root causes of spending in the upper deciles and how much reflects needed services rather than poor quality of care, medical errors, avoidable hospital and emergency room care due to delayed receipt of needed ambulatory services, and unnecessary care-all of which could in principle be addressed through programmatic changes.…”
Section: Discussion and Policy Implicationsmentioning
confidence: 99%
“…8 are designed to make enrollment easier and target hard-to-reach populations by simplifying and translating enrollment forms.…”
Section: Discussionmentioning
confidence: 99%
“…Statistically significant differences in prevalence at P Ͻ .05. in 2001 to 65.8% in 2005.12 Between 2001 and 2005-2006, the proportion of CSHCN who were covered by private insurance declined at an even more rapid rate, from 65.1% to 59.3% 8. In understanding the importance of the shift in public and private coverage, it is worth noting that contrary to prevailing assumptions, the 2005-2006 survey data show that publicly insured CSHCN are slightly more likely to achieve the health insurance core outcome than privately insured CSHCN.…”
mentioning
confidence: 99%